PEMERIKSAAN ESOFAGOFRAFI PADA PASIEN DENGAN KLINIS CORPUS ALIENUM DI RSJ PROF. Dr. SOEROJO MAGELANG - Mufida, Widya; Yusnida, Arnefia Mei; Utami, Mega; Faesol, Ahmad (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The Antero Posterior (AP) Plain, Lateral Plain, Contrast AP, and Left Posterior Oblique (LPO) projections are used in esophagography examinations with clinical corpus alienum at the Radiology Installation of Prof. Dr. Soerojo Psychiatric Hospital Magelang. The contrast medium is water soluble iodine mixed with warm water in a 1: 1 ratio up to 200 ml. The purpose of this study is to determine the reasons for using lateral projections to see the patient's preparation before inserting contrast media in the clinical corpus alienum esophagography radiographic examination procedure. The research design was case study research with qualitative data, which was carried out at the Radiology Installation of Prof. Dr. Soerojo Psychiatric Hospital Magelang. The research was conducted from December 2021 until July 2022. The subjects of this study were one radiologist and three radiographers. The data was collected through observation, interviews, and documentation. Data analysis was carried out in some stages such as data collection, data reduction, data presentation, discussion and conclusion. The findings revealed that the esophagography examination procedure with clinical corpus alienum at Prof. Dr. Soerojo Psychiatric Hospital Magelang was performed without any special preparation. Only metal objects that may interfere with the radiographic image must be removed. Contrast media is administered orally by giving the patient a single dose, then holding the second fluid in the mouth until the radiographer instructs the patient to swallow. The Antero Posterior (AP) Plain and Lateral Plain projections are used before inserting contrast media to see the patient's preparation, determine the appropriate exposurefactor, and view the corpus alienum not only from the front side (AP projection), but also from the side (Lateral projection). The hope is that the corpus alienum can be seen without the need for esophagography, which is done with consideration for the patient's uncooperative condition